2014
DOI: 10.1016/j.nimb.2013.12.040
|View full text |Cite
|
Sign up to set email alerts
|

Ion beam analysis, corrosion resistance and nanomechanical properties of TiAlCN/CNx multilayer grown by reactive magnetron sputtering

Abstract: Abstract:A novel TiAlCN/CN x multilayer coating, consisting of nine TiAlCN/CN x periods with a top layer 0.5 m of CN x , was designed to enhance the corrosion resistance of CoCrMo biomedical alloy. The multilayers were deposited by dc and RF reactive magnetron sputtering from Ti 0.5 Al 0.5 and C targets respectively in a N 2 /Ar plasma. The corrosion resistance and mechanical properties of the multilayer coatings were analyzed and compared to CoCrMo bulk alloy. Ion beam analysis (IBA) and X-ray diffraction te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…The corrosion resistance of CoCrMo coated with TiN/TiAlN multilayers is better than the CoCrMo alloy coated with TiN or TiAlN single coatings [23]. In a previous work we reported that a similar multilayer of TiAlCN/CNx multilayer improved the mechanical properties and the corrosion resistance of CoCrMo [30]. Therefore, in the current work we hypothesize that multilayers of TiAlVCN/CNx may combine the excellent mechanical tribological characteristics of the ceramic crystalline layers of (TiAlVC)N with the low friction and improved adhesion of the amorphous CNx layers [19,31].…”
Section: Introductionmentioning
confidence: 84%
See 1 more Smart Citation
“…The corrosion resistance of CoCrMo coated with TiN/TiAlN multilayers is better than the CoCrMo alloy coated with TiN or TiAlN single coatings [23]. In a previous work we reported that a similar multilayer of TiAlCN/CNx multilayer improved the mechanical properties and the corrosion resistance of CoCrMo [30]. Therefore, in the current work we hypothesize that multilayers of TiAlVCN/CNx may combine the excellent mechanical tribological characteristics of the ceramic crystalline layers of (TiAlVC)N with the low friction and improved adhesion of the amorphous CNx layers [19,31].…”
Section: Introductionmentioning
confidence: 84%
“…It has: a metal layer of TiAlV to promote adhesion of the multilayer, 9 layers of CNx alternating with 9 layers of TiAlVCN and finally a relatively thick CNx layer deposited on the top of the multilayer to reduce the coating COF [16]. Based on prior work by our group, the total thickness of the multilayer has been chosen to be from 3.0 to 3.5 µm [30]. [16,37].…”
Section: Materials and Experimental Proceduresmentioning
confidence: 99%
“…Figure 7 shows a statistical analysis of the electrolytes used in the reports related to MeN-, MeCN-, and a-C-based coatings proposed for different biomedical applications. As depicted in Figure 7 some of the papers used simple saline solutions containing NaCl, with varying concentrations of the salt (from 0.9% [11,87,100,104], which resembles the physiological concentration, up to 3% of NaCl [103]), while the other electrolytes were represented by more complex saline solutions (phosphate buffer solution (PBS) [81,105], Hank's balanced saline solution (HBSS) [52,57], or simulated body fluid (SBF) [12,92,106,107]), which can contain some organic molecules such as in Tyrode"s simulated body fluid and AFNOR S90-701 artificial saliva [19,102] and Fusayama Mayer artificial saliva [101]. The addition of proteins to SBF was also performed.…”
Section: Corrosion Behaviour Of Coatings In Simulated Body Fluids Andmentioning
confidence: 99%
“…As a matter of fact, nanocomposite coating design has been widely applied to improve the toughness, adhesion, mechanical and tribological properties [11][12][13] . Furthermore, multilayer coating designs composed of sub-layers in nanometer scales were also developed to improve performance under the dry machining because the multiple and nanoscale interfaces could inhibit the propagation of cracks, lower the residual stress, increase the adhesion strength as well as hardness, with example including TiAlN/VN 14 Carbon doped TiAlN coatings or TiAlCN coating, has also been frequently reported 18,19 . For carbon-doped TiAlN coatings, the structure changed from NaCl-type phase to a nano-composite structure with increasing C content, and the friction coefficient decreased from 0.8 to 0.19 when the C content reached 26.69 at.%.…”
Section: Introductionmentioning
confidence: 99%